Contribution to the study of improving the aesthetics of the smile by repairing and reshaping the incisors with composite materials. - Stoica Alexandra Mihaela; Stoica Oana Elena; Kovacs-Ivacson Csinszka; Monea Monica Dana ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2021)
Introduction. Dental aesthetics, although it seems something relative and difficult to evaluate, it is governed by a series of laws and rules that connect the dental disciplines, creating a unitary whole. It is structured by rules, perfected by artistic sense and by the inclination towards beauty of all specialists in dento-facial cosmetics.